Modulation of bone morphogenetic protein activity by melatonin in ovarian steroidogenesis - Fumio Otsuka (Reproductive Medicine and Biology, 2018)
Abstract Background Melatonin regulates circadian and seasonal rhythms and the activities of hormones and cytokines that are expressed in various tissues, including the ovary, in which melatonin receptors are expressed. In the ovary, follicular growth occurs as a result of complex interactions between pituitary gonadotropins and autocrine and paracrine factors, including bone morphogenetic proteins (BMPs) that are expressed in the ovary. Methods The effects of melatonin and BMPs on steroidogenesis were examined by using the primary cultures of rat granulosa cells. Main findings (Results) It was shown that melatonin has antagonistic effects on BMP‐6 actions in the granulosa cells, suggesting that melatonin is likely to contribute to balancing the biological activity of endogenous BMPs that maintain progesterone production and luteinization in the growing follicles. Similar interactions between melatonin and BMP–smad signaling also were shown in the mechanism of controlling ovarian steroidogenesis by other ligands. Conclusion A new role of melatonin in the regulation of endocrine homeostasis in relation to BMP activity is introduced in this review.